Posso seguir o gps?: usos e apropriações de aplicativos de transporte para experimentação da cidade de Fortaleza - Monteiro Filho, José Lemos (2022)
This research aims to study the impact of transport applications in the lives of residents of Fortaleza, capital of Ceará, in order to determine how the uses and appropriations (CANCLINI) of these new technologies to experiment (MONGIN) the urban space (CANEVACCI) from the capital of Ceará. The research focus was based on the experiences that were related by the users interviewed in this investigation, therefore, it is not limited to any specific mobile application (Uber, 99, inDriver, Sinditaxi, Vyse, Lady Driver, among others). With the purpose of establishing an introductory cut about the advent and evolution of technologies such as mobility applications, there was a transdisciplinary bibliographic contribution, which included the reading and analysis of works from areas, as for instance, Sociology, Anthropology and Geography. Subsequently, the research acquired an ethnographic character (GUBER; WINKIN) with the performance of the following methodological procedures: a) participant observation (ANGROSINO) made by the researcher in the condition of passenger in trips around the city using the transport applications; b) application of an online application with open questions about habits in the routines of use of transport applications; c) and conducting interviews with 12 users, each of whom lives in a different regional in the capital of Ceará. In conclusion, the urban transportation apps, through their operations in Fortaleza, transform how people look and perceive the city, giving a new meaning to social practices and contributing to the (re)discovery of places, situations of violence and urban circulation dynamics.